Melanoma bone metastasis-induced osteocyte ferroptosis via the HIF1α-HMOX1 axis - Yewei Jia; Rui Li; Yixuan Li; Katerina Kachler; Xianyi Meng; Andreas Gießl; Yi Qin; Fulin Zhang; Ning Liu; Darja Andreev; Georg Schett; Aline Bozec (Bone Research)
Abstract Osteocytes are the main cells in mineralized bone tissue. Elevated osteocyte apoptosis has been observed in lytic bone lesions of patients with multiple myeloma. However, their precise contribution to bone metastasis remains unclear. Here, we investigated the pathogenic mechanisms driving melanoma-induced osteocyte death. Both in vivo models and in vitro assays were combined with untargeted RNA sequencing approaches to explore the pathways governing melanoma-induced osteocyte death. We could show that ferroptosis is the primary mechanism behind osteocyte death in the context of melanoma bone metastasis. HMOX1 was identified as a crucial regulatory factor in this process, directly involved in inducing ferroptosis and affecting osteocyte viability. We uncover a non-canonical pathway that involves excessive autophagy-mediated ferritin degradation, highlighting the complex relationship between autophagy and ferroptosis in melanoma-induced osteocyte death. In addition, HIF1α pathway was shown as an upstream regulator, providing a potential target for modulating HMOX1 expression and influencing autophagy-dependent ferroptosis. In conclusion, our study provides insight into the pathogenic mechanisms of osteocyte death induced by melanoma bone metastasis, with a specific focus on ferroptosis and its regulation. This would enhance our comprehension of melanoma-induced osteocyte death.